Hierarchical pore sound-absorbing microsphere, preparation method thereof and sound-absorbing device

By uniformly mixing zeolite molecular sieves, inorganic binders, etc. and curing them in a hot oil column, a multi-stage pore structure sound-absorbing microspheres are formed, which solves the problems of micropore blockage and poor spherical shape in the existing sound-absorbing microsphere preparation methods, and achieves efficient sound-absorbing performance and low-cost industrial production.

CN119793344APending Publication Date: 2025-04-11YONGJIANG LAB
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411896519.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing preparation methods for sound-absorbing microspheres are prone to clogging micropores, poor spherical shape, and uneven particle size, resulting in a significant increase in mass transfer resistance of sound-absorbing materials, making it difficult to meet the high requirements of mobile phones and smart devices for sound-absorbing materials performance.

Method used

Zeolite molecular sieve, inorganic binder, water-soluble polymer material, coagulant and inorganic solvent are uniformly mixed, adjusted to acidity, and formed a mixed slurry. Then, the slurry is added to the hot oil column by droplet generator, and heat-cured to obtain composite microspheres. Finally, multi-stage pore sound-absorbing microspheres are formed by calcination.

Benefits of technology

The prepared multi-stage pore sound-absorbing microspheres have good spherical shape, are not easy to rub off powder, have good sound-absorbing performance, and are low in production costs, which are suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793344A_ABST
    Figure CN119793344A_ABST
Patent Text Reader

Abstract

The invention provides a hierarchical pore sound-absorbing microsphere, a preparation method thereof and a sound-absorbing device. The method for preparing the hierarchical pore sound-absorbing microspheres comprises the following steps: uniformly mixing a zeolite molecular sieve, an inorganic binder, a water-soluble polymer material, a coagulant and an inorganic solvent, and adjusting to acidity to obtain mixed slurry, the water-soluble polymer material having a thermal swelling characteristic; dropwise adding the mixed slurry into a hot oil column by using a liquid drop generator, and heating and curing to obtain composite microspheres; and calcining the composite microspheres to obtain the hierarchical porous sound-absorbing microspheres. The prepared hierarchical-pore sound-absorbing microspheres comprise rich micropores, mesopores and macropores, the air compliance of the microspheres can be obviously improved, air can enter and exit the micropores more smoothly and quickly, the actual use efficiency of the micropores is improved, and therefore the low-frequency response is improved; the hierarchical-pore sound-absorbing microspheres prepared by the method are good in sphericity degree and not prone to powder falling due to friction, the production cost is low, the method is easy to implement and operate, and industrial mass production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical materials, and in particular to multi-level hole sound-absorbing microspheres, a preparation method thereof and a sound-absorbing device. Background Art

[0002] Silica-alumina molecular sieve material has abundant micropores. The molecular sieve is bonded with a polymer binder to form a composite microsphere material (N'Bass sound-absorbing material) and filled into the rear sound cavity of the mobile phone speaker. The abundant micropores are used to adsorb and compress the air, which doubles the virtual sound of the speaker rear cavity and greatly improves the low-frequency response. However, with the development of miniaturization, lightness, and intensiveness of mobile phones and smart wearable devices, higher requirements are placed on the performance of sound-absorbing materials.

[0003] At present, the preparation method of sound-absorbing microspheres mostly uses organic binders and silicon-aluminum molecular sieves to make a slurry, and then spray-drying is used to make spherical particles. The molding process in this preparation method is easy to cause blockage of micropores, and the microspheres prepared by spray drying have poor sphericity and uneven particle size, which are easy to rub off powder, and the particles are unevenly stacked and relatively compact. It is difficult to form unobstructed channels between particles, resulting in a significant increase in the overall mass transfer resistance of the sound-absorbing material.

[0004] Therefore, the preparation method of multi-level porous sound-absorbing microspheres needs further research. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a method for preparing a multi-level porous sound-absorbing microsphere, wherein the multi-level porous sound-absorbing microsphere prepared by the method has a pore structure of micropores, mesopores and macropores, and the multi-level porous sound-absorbing microsphere has good sphericity and is not easy to lose powder due to friction.

[0006] In one aspect of the present invention, the present invention provides a method for preparing multi-level porous sound-absorbing microspheres. According to an embodiment of the present invention, the method for preparing multi-level porous sound-absorbing microspheres includes: uniformly mixing zeolite molecular sieves, inorganic binders, water-soluble polymer materials, coagulants and inorganic solvents, and adjusting to acidity to obtain a mixed slurry, wherein the water-soluble polymer material has a thermal swelling property; using a droplet generator to drop the mixed slurry into a hot oil column, and heat-curing to obtain composite microspheres; calcining the composite microspheres to obtain the multi-level porous sound-absorbing microspheres. Thus, after the mixed slurry is dripped into the hot oil column, the water-soluble polymer material in the mixed slurry is heated to swell and spread throughout the droplets of the mixed slurry to form a gel. On the one hand, the gel can be used as a template to form mesopores and macropores through subsequent calcination. On the other hand, the gas generated by the thermal decomposition of the coagulant forms continuous macropores in the gel during the escape process. In the preparation method, an inorganic binder is used, and the multi-level pore sound-absorbing microspheres are bonded by the inorganic binder. The inorganic binder has a loose porous structure and is not easy to block the micropores of the molecular sieve. It can improve the micropore utilization rate of the multi-level pore sound-absorbing particles to a greater extent and improve the low-frequency performance. The multi-level pore sound-absorbing microspheres prepared by the above method have good sphericity, are not easy to rub off powder, and have a low production cost. The method is easy to implement and is convenient for industrial mass production.

[0007] According to an embodiment of the present invention, based on the total mass of the mixed slurry, the mixed slurry includes: 10%-45% of the zeolite molecular sieve; 1%-40% of the inorganic binder; 0.1%-4% of the water-soluble polymer material; 1%-10% of the coagulant; and the remainder of the inorganic solvent.

[0008] According to an embodiment of the present invention, the water-soluble polymer material includes natural polymer materials and / or synthetic polymer materials, wherein the synthetic polymer material includes at least one of polyacrylic acid resin, polyacrylamide, and methyl cellulose, and the natural polymer material includes at least one of starch, cellulose, chitin, inulin, and glycogen.

[0009] According to an embodiment of the present invention, the method for preparing multi-level porous sound-absorbing microspheres also satisfies at least one of the following conditions: the zeolite molecular sieve is a silica-alumina molecular sieve, and the structure type of the zeolite molecular sieve includes at least one of FER, MFI, CHA, MEL or MTW; the inorganic binder includes at least one of silica sol, aluminum sol, silica-alumina sol or sodium silicate; the coagulant includes at least one of triethylamine, ethylenediamine, triethylenediamine, hexamethylenetetramine, and urea, and optionally, the molar ratio of silicon atoms and / or aluminum atoms in the inorganic binder to the coagulant is 1: (0.05-0.2); optionally, the solid content of the inorganic binder is 3% to 20%.

[0010] According to an embodiment of the present invention, the pH of the mixed slurry is 3-5.

[0011] According to an embodiment of the present invention, the oil temperature in the hot oil column is 40-120° C., and / or the oil column height of the hot oil column is 2 m-5 m.

[0012] According to an embodiment of the present invention, the calcination treatment temperature is 500° C.-800° C., the heating rate is 60° C. / h-300° C. / h, and the calcination time is 1h-4h.

[0013] In another aspect of the present invention, the present invention provides a multi-level pore sound-absorbing microsphere. According to an embodiment of the present invention, the multi-level pore sound-absorbing microsphere is prepared by the method described above, and micropores, mesopores and macropores are formed in the multi-level pore sound-absorbing microsphere, the micropores are distributed in the zeolite molecular sieve, and the mesopores and the macropores extend inside and / or on the surface of the multi-level pore sound-absorbing microsphere. As a result, the multi-level pore sound-absorbing microsphere has good sphericity, is not easy to rub off powder, and has good sound absorption performance. It can be understood by those skilled in the art that the multi-level pore sound-absorbing microsphere has all the characteristics and advantages of the method for preparing sound-absorbing microspheres described above, and no more details are given here.

[0014] According to an embodiment of the present invention, the particle size of the multi-level porous sound-absorbing microsphere is 0.10mm-10mm, wherein the pore size of the micropore is 0.4nm-0.7nm, the pore size of the mesopore is 2nm-10nm, and the pore size of the macropore is 0.5μm-50μm.

[0015] According to an embodiment of the present invention, the pore volume ratio of the micropores, the mesopores and the macropores is (0.1-0.15):(0.1-0.3):(1.2-1.8).

[0016] In another aspect of the present invention, the present invention provides a sound absorbing device. According to an embodiment of the present invention, the sound absorbing device includes the multi-level hole sound absorbing microspheres prepared by the method described above, or the sound absorbing device includes the multi-level hole sound absorbing microspheres described above. Therefore, the sound absorbing device has a good sound absorbing effect and improves its low-frequency effect. It can be understood by those skilled in the art that the sound absorbing device has all the features and advantages of the multi-level hole sound absorbing microspheres described above, and no further elaboration is given here. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0018] Figure 1 The present invention is a flowchart of a method for preparing multi-level hole sound-absorbing microspheres in one embodiment of the present invention.

[0019] Figure 2 This is a scanning electron microscope image of the multi-level hole sound-absorbing microsphere obtained in Example 4;

[0020] Figure 3 This is a scanning electron microscope image of the multi-level hole sound-absorbing microsphere obtained in Comparative Example 1;

[0021] Figure 4 This is a scanning electron microscope image of the multi-level porous sound-absorbing microspheres obtained in Comparative Example 3. DETAILED DESCRIPTION

[0022] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0023] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0024] In a method for preparing multi-level hole sound-absorbing microspheres of the present invention. According to an embodiment of the present invention, referring to Figure 1 , the method for preparing multi-level hole sound-absorbing microspheres comprises:

[0025] S100: uniformly mixing zeolite molecular sieve, inorganic binder, water-soluble polymer material, coagulant and inorganic solvent, and adjusting to acidity to obtain a mixed slurry, wherein the water-soluble polymer material has a thermal swelling property.

[0026] According to some embodiments of the present invention, based on the total mass of the mixed slurry, the mixed slurry includes: 10%-45% (for example, 10%, 12%, 15%, 17%, 20%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 42%, 45%, etc.) of zeolite molecular sieve; 1%-40% (for example, 1%, 3%, 5%, 7%, 10%, 12%, 15%, 17%, 20%, 22%, etc.) of zeolite molecular sieve; %, 25%, 28%, 30%, 32%, 35%, 37%, 40%, etc.) of inorganic binder; 0.1%-4% of water-soluble polymer material (such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc.); 1%-10% (such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.) of coagulant; and the remainder of inorganic solvent. The mixed slurry in the above proportions is helpful to obtain multi-level porous sound-absorbing microspheres with good performance; and it can be seen that in the present invention, only a small amount of water-soluble polymer material (i.e., a small amount of template agent) needs to be added to form a multi-level pore structure in the multi-level porous sound-absorbing microspheres, which can significantly reduce costs.

[0027] In some embodiments of the present invention, the molar ratio of silicon atoms and / or aluminum atoms in the inorganic binder to the coagulant is 1:(0.05-0.2), such as a molar ratio of 1:0.05, 1:0.08, 1:0.1, 1:0.12, 1:0.14, 1:0.15, 1:0.16, 1:0.18, 1:0.2, etc. Therefore, the above ratio requirement is conducive to obtaining microspheres with good particle sphericity. In the subsequent steps, after the mixed slurry droplets are added to the hot oil column, the coagulant releases ammonia gas when heated, which increases the pH of the droplets, causing the inorganic adhesive gel to solidify and the droplets to become microspheres. If the amount of coagulant is relatively too little, the droplets are not completely solidified when they reach the bottom of the oil column, and the accumulation and extrusion cannot form a sphere. If the amount of coagulant is relatively too high, a large amount of gas (ammonia and formaldehyde released by the coagulant) is generated, which will impact the spherical particles and make the sphericity relatively worse.

[0028] According to an embodiment of the present invention, the pH of the mixed slurry is 3-5, such as pH 3, 3.5, 4, 4.5, 5, etc. The above acidic adjustment is helpful to form good spherical particles. If the pH is too high, the viscosity of the mixed slurry will be relatively large, which is easy to clog the droplet generator.

[0029] In some embodiments of the present invention, the pH of the mixed slurry can be adjusted by one or more of inorganic acids such as hydrochloric acid, nitric acid, phosphoric acid, and / or organic acids such as salicylic acid, acetic acid, oxalic acid, and the like.

[0030] It should be noted that when calculating the ratio of the various components of the above-mentioned mixed slurry, the amount of acid solution is not taken into account.

[0031] In some embodiments of the present invention, the inorganic solvent may include water.

[0032] In some embodiments of the present invention, the zeolite molecular sieve is a silica-alumina molecular sieve, and the silica-alumina molecular sieve structure type includes one or more of FER, MFI, CHA, MEL and MTW. In some specific embodiments, the silica-alumina molecular sieve type is an MFI structure, and the silicon-alumina ratio is greater than 200. The above zeolite molecular sieve has a good microporous structure, which can help to realize the multi-level pore structure of the sound-absorbing microspheres.

[0033] In some embodiments of the present invention, the inorganic binder includes at least one of silica sol, aluminum sol, silica aluminum sol or sodium silicate. After being formed, the above-mentioned inorganic binder exists in the form of nanoparticle accumulation, and the accumulation of particles forms mesopores, so it is not easy to cause blockage of micropores in the zeolite molecular sieve.

[0034] In some embodiments, the solid content of the inorganic binder is 3% to 20%, for example, 3%, 5%, 7%, 9%, 10%, 12%, 15%, 17%, 20%, etc.

[0035] In some embodiments of the present invention, the coagulant includes at least one of triethylamine, ethylenediamine, triethylenediamine, hexamethylenetetramine, and urea. The coagulant is easily decomposed to generate gas at the oil temperature of the hot oil column, and the generated ammonia can increase the pH of the mixed slurry, thereby solidifying the inorganic binder gel and promoting the formation of spherical particles.

[0036] In some embodiments of the present invention, the water-soluble polymer material includes natural polymer materials and / or synthetic polymer materials, wherein the synthetic polymer material includes at least one of polyacrylic acid resin, polyacrylamide, and methylcellulose, and the natural polymer material includes at least one of starch, cellulose, chitin, inulin, and glycogen. The above-mentioned water-soluble polymer material has good swelling properties, and the gel formed after swelling can be used as a good template to form a good mesoporous and macroporous structure; and by adding a small amount of the above-mentioned template, a multi-level pore structure can be formed in the sound-absorbing microspheres, which can significantly reduce the cost; and the material source is wide, and the purchase price is low, which can further reduce the production cost.

[0037] Among them, when the water-soluble polymer material includes polyacrylic acid resin, there is no special requirement for the specific material of polyacrylic acid resin, and technical personnel in this field can flexibly select it according to actual needs. For example, it can be polymethyl methacrylate. When adding, it can be added in the form of polymethyl methacrylate microsphere emulsion.

[0038] S200: using a droplet generator to drop the mixed slurry into the hot oil column, and heat-curing to obtain composite microspheres. In this process, the added mixed slurry droplets are heated and gelled to solidify into particles, that is, composite microspheres are obtained.

[0039] According to some embodiments of the present invention, the oil temperature in the hot oil column is 40-120° C., for example, the oil temperature is 40° C., 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., etc. At the above oil temperature, the added mixed slurry is heated and solidified into particles to obtain composite microspheres.

[0040] According to some embodiments of the present invention, the height of the hot oil column is 2m-5m, such as 2m, 2.5m, 3m, 3.5m, 4m, 4.5m, 5m, etc.

[0041] According to some embodiments of the present invention, the molding oil in the hot oil column is one or more of lubricating oil, diesel, gasoline, vegetable oil, vacuum pump oil, machine oil, and spindle oil.

[0042] According to some embodiments of the present invention, after the composite microspheres are aged for a certain period of time, the particles can be scooped out with a filter and washed with anhydrous ethanol to remove oil stains on the surface of the particles to obtain wet particles; the wet particles are then dried to remove moisture to obtain dry composite microspheres. In some embodiments, the aging time can be 1 to 5 hours.

[0043] In some embodiments, the temperature for drying the wet particles may be 40-100° C. and the drying time may be 6-12 hours. Under the above conditions, the moisture in the composite microspheres can be removed well without causing damage to the composite microspheres.

[0044] S300: calcining the composite microspheres to obtain multi-level pore sound-absorbing microspheres.

[0045] According to some embodiments of the present invention, the calcination temperature is 500°C-800°C (for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.), the heating rate is 60°C / h-300°C / h (for example, 60°C / h, 100°C / h, 150°C / h, 200°C / h, 250°C / h, 300°C / h, etc.), and the calcination time is 1h-4h. Under the above conditions, organic substances such as polymers in the composite microspheres are decomposed to form a macroporous structure, and at the same time, the components such as silicon oxide and aluminum oxide in the molecular sieve and the inorganic binder are not damaged.

[0046] According to an embodiment of the present invention, after the mixed slurry is dripped into the hot oil column, the water-soluble polymer material in the mixed slurry is heated to swell thermally and spread throughout the droplets of the mixed slurry to form a gel. On the one hand, the gel can be used as a template to form mesopores and macropores through subsequent calcination. On the other hand, the gas generated by the thermal decomposition of the coagulant forms continuous macropores in the gel during the escape process. In the preparation method, an inorganic binder is used, and the multi-level pore sound-absorbing microspheres are bonded by the inorganic binder. The inorganic binder has a loose porous structure and is not easy to block the micropores of the molecular sieve. It can improve the micropore utilization rate of the multi-level pore sound-absorbing particles to a greater extent and improve the low-frequency performance. The multi-level pore sound-absorbing microspheres prepared by the above method have good sphericity, are not easy to rub off powder, and have a low production cost. The method is easy to implement and operate, and is convenient for industrial mass production.

[0047] In some embodiments of the present invention, the multi-level pore sound-absorbing microspheres prepared by the above method include zeolite molecular sieves and inorganic adhesive particles, and the inorganic adhesive particles adhere the zeolite molecular sieves together. The multi-level pore sound-absorbing microspheres are formed with abundant micropores, mesopores and macropores, which can significantly improve the air compliance of the microspheres, so that the air can enter and exit the micropores more smoothly and quickly, improve the actual use efficiency of the micropores, and thus improve the low-frequency response. Among them, the micropores in the multi-level pore sound-absorbing microspheres are the micropores in the zeolite molecular sieve, that is, the micropores are distributed in the zeolite molecular sieve; some mesopores are pores generated by the accumulation of particles such as inorganic adhesives and zeolite molecular sieves, and the macropores and some mesopores are pores formed by the calcination of the template and the escape of gas during the microsphere forming process, so the mesopores and macropores extend inside and / or on the surface of the multi-level pore sound-absorbing microspheres.

[0048] In some embodiments of the present invention, the pore size of the micropore is 0.4nm-0.7nm, the pore size of the mesopore is 2nm-10nm, and the pore size of the macropore is 0.5μm-50μm. In some embodiments of the present invention, the pore volume ratio of micropores, mesopores and macropores is (0.1-0.15):(0.1-0.3):(1.2-1.8), for example, the pore volume ratio of micropores, mesopores and macropores is 0.1:0.1:1.2, 0.1:0.2:1.5, 0.12:0.2:1.5, 0.15:0.3:1.2, 0.15:0.2:1.8, 0.1:0.2:1.8, 0.15:0.1:1.8, 0.15:0.1:1.2, etc. It can be seen that the multi-level porous sound-absorbing microspheres of the present invention have a suitable proportion of micropores, mesopores and macropores, which can improve the micropore utilization rate of the multi-level porous sound-absorbing particles to a greater extent and improve the low-frequency performance.

[0049] In some embodiments of the present invention, the preparation method can be used to obtain multi-level porous sound-absorbing microspheres with a particle size of 0.10-10 mm, which are uniform in size and high in sphericity. The microspheres are in point contact with each other and are evenly stacked, which is beneficial to reducing air resistance. The high sphericity is beneficial to reducing wear and preventing the microspheres from falling off.

[0050] In another aspect of the present invention, the present invention provides a multi-level porous sound-absorbing microsphere. According to an embodiment of the present invention, the multi-level porous sound-absorbing microsphere is prepared by the method described above, and micropores, mesopores and macropores are formed in the multi-level porous sound-absorbing microsphere, the micropores are distributed in the zeolite molecular sieve, and the mesopores and macropores extend inside and / or on the surface of the multi-level porous sound-absorbing microsphere. As a result, the multi-level porous sound-absorbing microsphere has good sphericity, is not easy to rub off powder, and has good sound absorption performance. It can be understood by those skilled in the art that the multi-level porous sound-absorbing microsphere has all the characteristics and advantages of the method for preparing multi-level porous sound-absorbing microspheres described above, and no excessive elaboration is required here.

[0051] In another aspect of the present invention, the present invention provides a sound absorbing device. According to an embodiment of the present invention, the sound absorbing device includes the multi-level hole sound absorbing microspheres prepared by the method described above, or the sound absorbing device includes the multi-level hole sound absorbing microspheres described above. Therefore, the sound absorbing device has a good sound absorbing effect and improves its low-frequency effect. It can be understood by those skilled in the art that the sound absorbing device has all the features and advantages of the multi-level hole sound absorbing microspheres described above, and no further elaboration is given here.

[0052] In some embodiments of the present invention, there is no restriction on the application field of the sound absorbing device, and those skilled in the art can flexibly select according to actual needs. In some embodiments, the sound absorbing device can be applied to gymnasiums, cinemas, KTVs, concert halls, theaters, classrooms, libraries, hotels, and display devices (mobile phones, computers, iPads, game consoles, etc.).

[0053] Example

[0054] Example 1

[0055] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, and 3 g of polymethyl methacrylate microsphere emulsion (solid content of 15%), mix them thoroughly, add 1.5 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0056] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0057] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0058] Example 2

[0059] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200 and 6 g of polymethyl methacrylate microsphere emulsion (solid content of 15%), mix them well, add 1.5 g of hexamethylenetetramine to fully dissolve them, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0060] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0061] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0062] Example 3

[0063] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, and 9 g of polymethyl methacrylate microsphere emulsion (solid content of 15%), mix them thoroughly, add 1.5 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0064] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0065] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0066] Example 4

[0067] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200 and 12 g of polymethyl methacrylate microsphere emulsion (solid content of 15%), mix them well, add 1.5 g of hexamethylenetetramine to fully dissolve them, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0068] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0069] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0070] Example 5

[0071] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, and 1.2 g of polyacrylamide, mix them well, add 1.5 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0072] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0073] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0074] Example 6

[0075] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200 and 2 g of methyl cellulose, mix them evenly, add 1.5 g of hexamethylenetetramine to fully dissolve them, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0076] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0077] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0078] Example 7

[0079] Weigh 15 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 45 g of deionized water, 40 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, and 12 g of polymethyl methacrylate microsphere emulsion (solid content of 15%), mix them thoroughly, add 2.4 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0080] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0081] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0082] Comparative Example 1

[0083] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, and 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, mix them well, add 1.5 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0084] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0085] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0086] Comparative Example 2

[0087] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, and 5 g of 200-mesh activated carbon (template agent), mix them well, add 1.5 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0088] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0089] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0090] Comparative Example 3

[0091] Weigh 30 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 34 g of deionized water, 36 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, and 10 g of 200-mesh activated carbon, mix them thoroughly, add 1.5 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0092] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0093] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0094] Comparative Example 4

[0095] Weigh 15 g of silica sol (HS-30, solid content of 30%, average particle size of silicon oxide particles of 12 nm), 45 g of deionized water, and 40 g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 200, mix them well, add 2.4 g of hexamethylenetetramine to fully dissolve, and then adjust the pH of the slurry to 3-5 with concentrated hydrochloric acid to obtain a mixed slurry;

[0096] The mixed slurry was dripped into 100°C machine oil using a droplet generator to form the mixture. After standing for 2 hours, the formed balls were taken out from the oil, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60°C for 12 hours to obtain dried composite microspheres.

[0097] The composite microspheres were calcined at 650°C for 4 hours to obtain multi-level pore sound-absorbing microspheres.

[0098] The comparison of parameters in the above embodiments and comparative examples can be seen in Table 1, and the test results of the pore distribution of the obtained sound-absorbing microspheres and their corresponding sound absorption frequencies can be seen in Table 2.

[0099] Acoustic properties The acoustic performance measurement method is as follows: use an impedance analyzer to test the resonant frequency of the speaker. First, connect a speaker with a back cavity volume of 0.4mL (0.4cc for short) to the impedance analyzer to test the resonant frequency F0 when the cavity is empty (i.e., without filling sound-absorbing microspheres). Then, multi-level hole sound-absorbing microspheres with a diameter of 300-500μm in the screened embodiments and comparative examples are taken, and 0.3cc is filled into the back cavity of the speaker to test the resonant frequency F0 after filling with the sound-absorbing microspheres. The difference between the resonant frequency after filling and the resonant frequency of the cavity is △F0. In general, the larger the △F0, the better the low-frequency response performance of the sound-absorbing material.

[0100] Pore ​​volume test method: The sample was pretreated in vacuum at 180°C for 24 h using a Micromeritic ASAP2460 gas adsorption instrument, and adsorbed with liquid nitrogen at -196°C. The mesopore volume was calculated using the BJH method and the micropore volume was calculated using the t-plot method. The macropore volume of the sample was tested using a MicroActive AutoPore V 9600 mercury intrusion instrument.

[0101] Table 1

[0102]

[0103] Table 2

[0104]

[0105]

[0106] The scanning electron microscope image of the multi-level hole sound-absorbing microspheres obtained in Example 4 can be referred to Figure 2 ,,The scanning electron microscope image of the multi-level hole sound-absorbing microsphere obtained in Comparative Example 1 can be referred to Figure 3 The scanning electron microscope image of the multi-level hole sound-absorbing microsphere obtained in Comparative Example 3 can be referred to Figure 4 .

[0107] From the data and electron microscope images of the above embodiments and comparative examples, it can be seen that by adding water-soluble polymer materials in the microsphere forming process, the gel template agent after thermal swelling can effectively increase the pore volume of mesopores and macropores in the multi-level porous microsphere particles, and its performance is also effectively improved; from the data of Examples 1 to 4, it can be seen that with the increase in the amount of water-soluble polymer materials, the pore volume of mesopores and macropores and the sound absorption performance of the obtained multi-level porous sound-absorbing microspheres are gradually improved, which can illustrate that the addition of water-soluble polymer materials can provide macropore channels for the multi-level porous sound-absorbing microspheres, thereby improving the low-frequency performance.

[0108] Compared with the activated carbon used as the template in Comparative Examples 2 and 3, by using a water-soluble polymer material with a thermal swelling effect as the template, only a small amount of water-soluble polymer material needs to be added to achieve the same or even better low-frequency improvement effect. Therefore, using a polymer material with a thermal swelling effect as a template is beneficial to reducing the amount of the template used, thereby reducing costs.

[0109] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0110] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing multi-level hole sound-absorbing microspheres, characterized in that: include: The zeolite molecular sieve, the inorganic binder, the water-soluble polymer material, the coagulant and the inorganic solvent are uniformly mixed and adjusted to be acidic to obtain a mixed slurry, wherein the water-soluble polymer material has a thermal swelling property; The mixed slurry is dripped into a hot oil column by using a droplet generator, and the mixed slurry is cured by heat to obtain composite microspheres; The composite microspheres are calcined to obtain the multi-level hole sound-absorbing microspheres.

2. The method according to claim 1, characterized in that Based on the total mass of the mixed slurry, the mixed slurry includes: 10%-45% of the zeolite molecular sieve; 1%-40% of the inorganic binder; 0.1%-4% of the water-soluble polymer material; 1%-10% of the coagulant; and The balance is inorganic solvent.

3. The method according to claim 1, characterized in that The water-soluble polymer material includes natural polymer material and / or synthetic polymer material, wherein: The synthetic polymer material includes at least one of polyacrylic acid resin, polyacrylamide and methyl cellulose. The natural polymer material includes at least one of starch, cellulose, chitin, inulin and glycogen.

4. The method according to claim 1, characterized in that: At least one of the following conditions is met: The zeolite molecular sieve is a silicon-aluminum molecular sieve, and the structure type of the zeolite molecular sieve includes at least one of FER, MFI, CHA, MEL or MTW; The inorganic binder includes at least one of silica sol, alumina sol, silica-alumina sol or sodium silicate; The coagulant comprises at least one of triethylamine, ethylenediamine, triethylenediamine, hexamethylenetetramine and urea. Optionally, the molar ratio of silicon atoms and / or aluminum atoms in the inorganic binder to the coagulant is 1:(0.05-0.2); Optionally, the solid content of the inorganic binder is 3% to 20%.

5. The method according to claim 1, characterized in that The pH of the mixed slurry is 3-5.

6. The method according to any one of claims 1 to 5, characterized in that: The oil temperature in the hot oil column is 40-120° C., and / or the oil column height of the hot oil column is 2m-5m.

7. The method according to any one of claims 1 to 5, characterized in that: The calcination treatment temperature is 500°C-800°C, the heating rate is 60°C / h-300°C / h, and the calcination time is 1h-4h.

8. A multi-level hole sound-absorbing microsphere, characterized in that: The multi-level pore sound-absorbing microsphere is prepared by the method described in any one of claims 1 to 7, wherein micropores, mesopores and macropores are formed in the multi-level pore sound-absorbing microsphere, the micropores are distributed in the zeolite molecular sieve, and the mesopores and the macropores extend inside and / or on the surface of the multi-level pore sound-absorbing microsphere.

9. The multi-level hole sound-absorbing microsphere according to claim 8, characterized in that: The particle size of the multi-level pore sound-absorbing microsphere is 0.10 mm-10 mm, wherein the pore size of the micropore is 0.4 nm-0.7 nm, the pore size of the mesopore is 2 nm-10 nm, and the pore size of the macropore is 0.5 μm-50 μm.

10. The multi-level hole sound-absorbing microsphere according to claim 8, characterized in that: The pore volume ratio of the micropores, the mesopores and the macropores is (0.1-0.15):(0.1-0.3):(1.2-1.8).

11. A sound absorbing device, characterized in that: The invention comprises a multi-level porous sound-absorbing microsphere prepared by the method according to any one of claims 1 to 7, or comprises a multi-level porous sound-absorbing microsphere according to any one of claims 8 to 10.

Citation Information

Cited By

  • Preparation method and application of flame-retardant sound-absorbing foaming material

    CN120623619A